AN EMPIRICAL ANALYSIS OF WORKFORCE DIVERSITY AND WORKPLACE INCLUSION ON EMPLOYEEMOTIVATION IN PRIVATE UNIVERSITIES IN NORTH INDIA - Ekta; Vaish, Vanshika; Mishra, Anjali; Bakshi, Megha (The journal of contemporary issues in business and government, 2023)
As globalization continues to advance, companies are employing a more diverse group of employees. This diversity is evident in educational institutions where staff and students comefrom different backgrounds and experiences, resulting in a range of ages, genders, and educational backgrounds. This has prompted the need to examine whether organizations are prepared to incorporate diversity into their culture. The impetus of this research is to look into the connection between Workplace Inclusion (WI), impact of Workplace Diversity (WD), and Employee Motivation (EM). It is becoming increasingly important for organizations to understand how these different perspectives can be leveraged to create more innovative solutions and foster better relationships between staff members. This research offers suggestions for enhancing workplace inclusiveness and reducing employee turnover through supportive initiatives. It also sheds light on how a common perception of inclusiveness can be formed and how an inclusive climate can help achieve diversity management goals. The results emphasize the critical role of programs that are sensitive to employee identity in promoting organizational commitment among a diverse workforce.